Handbook of chemical engineering calculations - Chopey, Nicholas P. (McGraw-Hill, 1994)
Physical and chemical properties; Stoichiometry; Phase equilibrium; Chemical-reaction equilibrium; Reaction kinetics and reactor design; Flow of fluids and solids; Heat transfer; Distillation; Extraction and leaching; Crystallization; Absorption and stripping; Liquid agitation; Size reduction; Filtration; Air-pollution control; Other chemical engineering calculations.